1999
DOI: 10.1021/tx9802365
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Activation of Diclofenac by Human Cytochrome P450 3A4:  Role of 5-Hydroxydiclofenac

Abstract: Cytochrome P450 2C11 in rats was recently found to metabolize diclofenac into a highly reactive product that covalently bound to this enzyme before it could diffuse away and react with other proteins. To determine whether cytochromes P450 in human liver could catalyze a similar reaction, we have studied the covalent binding of diclofenac in vitro to liver microsomes of 16 individuals. Only three of 16 samples were found by immunoblot analysis to activate diclofenac appreciably to form protein adducts in a NADP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(130 citation statements)
references
References 45 publications
(73 reference statements)
9
120
0
1
Order By: Relevance
“…These findings are supported by recent reports (Mohamadin et al, 2011;Zou et al, 2010) and considered attributable to the oxidative stress generated by co-treatment with LPS. Shen et al (1999) have reported that covalent binding of reactive metabolites of 5-OH-DCF to human liver microsomes was inhibited by GSH. Based on this finding, the decreased GSH level in hepatic tissues is considered to imply a reduced detoxication reaction of GSH with 5-OH-DCF reactive metabolites, resulting in increased adducts of the reactive metabolites to hepatic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by recent reports (Mohamadin et al, 2011;Zou et al, 2010) and considered attributable to the oxidative stress generated by co-treatment with LPS. Shen et al (1999) have reported that covalent binding of reactive metabolites of 5-OH-DCF to human liver microsomes was inhibited by GSH. Based on this finding, the decreased GSH level in hepatic tissues is considered to imply a reduced detoxication reaction of GSH with 5-OH-DCF reactive metabolites, resulting in increased adducts of the reactive metabolites to hepatic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Diclofenac is metabolized by the CYP enzymes 2C9 and 3A4, resulting in reactive metabolite(s) that bind to microsomal proteins [Naisbitt et al 2007;Bort et al 1999;Shen et al 1999]. Diclofenac-induced dose-and concentrationdependant liver injury has been demonstrated in rat hepatocytes [Kretzrommel and Boelsterli, 1993].…”
Section: Pharmacokinetic Changesmentioning
confidence: 99%
“…CYP2C11 was shown to be responsible for major diclofenac metabolisms, 4Ј-hydroxylation and 5-hydroxylation ( Fig. 1), in rat liver microsomes (Masubuchi et al, 2001), whereas distinct P450 isoforms, CYP2C9 and CYP3A4, were involved in these pathways, respectively, in human liver microsomes (Leemann et al, 1993;Shen et al, 1999;Tang et al, 1999b). Because CYP2C9 was not inactivated during diclofenac metabolism (Masubuchi et al, 2001), it was suggested that the inactivation of CYP2C11 was independent of 4Ј-hydroxylation pathway, supposing alternatively that 5-hydroxylation is involved in the inactivation of CYP2C11.…”
mentioning
confidence: 99%